Zirconato de cálcio: um estudo para aplicação como sensor de umidade relativa - Andre, Rafaela da Silveira (Universidade Federal de São Carlos, 2013)
In this work, it was used the Polymeric Precursors method (PPM). It started from a previous solution of metal cations in different concentrations, using citric acid as chelating agent and ethylene glycol as esterifying and polymerizing agent resulting in a dense resin. This resin was subjected to heat treatment at 300 ° C for a period of 4 hours for the pyrolysis of the obtained polyester resulting in amorphous compound. To obtain the crystalline powder, the amorphous compound was treated at different temperatures. The evolution of the crystallization process of CaZrO 3 and samples composition were accompanied by X-ray diffraction and Raman spectroscopy. The X-ray patterns obtained were refined with the Rietveld method. To identify the presence of defects and the morphology of the samples, it was used the UV-vis spectroscopy and scanning electron microscopy, respectively. To evaluate the sensor response, electrical measurements were performed showing that all samples showed CZO variation of electrical resistance against change in relative humidity. The methods of characterization showed structural differences in the samples as a function of composition variation of the system. The results indicate a transition from deep defects to light defects, due to the appearance of secondary phases in the system. Thus, according to the obtained results, the variation in composition may be used as a device to obtain materials with controlled optical properties and a more effective sensing and catalytic properties.
Keywords: Química; Zirconato de cálcio; Sensores de umidade; Fotoluminescência; CIENCIAS EXATAS E DA TERRA::QUIMICA